Desarrollo de una herramienta para el registro de estructuras cerebrales 3D utilizando técnicas de procesamiento de imágenes (Revista de Investigaciones Universidad del Quindío, 2014)
Medical image registration is one of the most important tasks in image guide surgery. It consists of finding a geometrical transformation that relates the points of images in order to correct for differences in size, position, orientation or spatial distortion that can occur, so it is possible a direct comparison between them to facilitate analysis by the specialist, either for diagnosis of a disease or for planning a stereotaxic surgery. In recent years multimodal registration techniques have been proposed, especially among images CT (computed tomography) and MRI (Magnetic Resonance Imaging). However, some problems still remain unsolved, and are therefore an active field of research. Due to problems of accuracy in models of rigid and non-rigid registration , which have not yet reached the precision required for neurosurgical applications, this article proposes the development of a tool for 3D brain registration using image processing techniques . The results show that a registration tool allows matching a given brain histological atlas of a particular patient. Besides, the developed system can be executed online, which benefits system functionality in neurosurgery procedures.
Keywords: Magnetic resonance image; computed tomography; brain atlas; image processing